2013
DOI: 10.1371/journal.pone.0058695
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Areas of the Visual Field Important for Quality of Life in Patients with Glaucoma

Abstract: PurposeThe purpose of this study was to create a vision-related quality of life (VRQoL) prediction system to identify visual field (VF) test points associated with decreased VRQoL in patients with glaucoma.MethodVRQoL score was surveyed in 164 patients with glaucoma using the ‘Sumi questionnaire’. A binocular VF was created from monocular VFs by using the integrated VF (IVF) method. VRQoL score was predicted using the ‘Random Forest’ method, based on visual acuity (VA) of better and worse eyes (better-eye and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 48 publications
2
91
2
6
Order By: Relevance
“…We speculate the fact that the participants in our study had better acuity (worse eye acuity was considered the best predictor of responses to reading questions in the Murata et al study) and tended not to be very advanced in their condition may be causes for this inconsistency. The prominence of the superior left of the VF, apparent in the Murata study, was not observed in our study, while Murata et al [19] found no indication of the inferior-left section of the VF being important. However, we theorise that this may be a result of the fact that reading in Japanese tategaki format goes from top-right to bottom-left rather than from top-left to bottom-right.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…We speculate the fact that the participants in our study had better acuity (worse eye acuity was considered the best predictor of responses to reading questions in the Murata et al study) and tended not to be very advanced in their condition may be causes for this inconsistency. The prominence of the superior left of the VF, apparent in the Murata study, was not observed in our study, while Murata et al [19] found no indication of the inferior-left section of the VF being important. However, we theorise that this may be a result of the fact that reading in Japanese tategaki format goes from top-right to bottom-left rather than from top-left to bottom-right.…”
Section: Discussioncontrasting
confidence: 87%
“…Murata et al [19] observed that the inferior field is the main area of importance for reading, much like the results of this research, but their region is closer to fixation. We speculate the fact that the participants in our study had better acuity (worse eye acuity was considered the best predictor of responses to reading questions in the Murata et al study) and tended not to be very advanced in their condition may be causes for this inconsistency.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…25 The locality of an IVF defect might be much more important than a summary measure and there are some imaginative studies that have highlighted this. 26 We have recently attempted to derive clinically meaningful estimates of the prevalence of different types of binocular visual field loss, because this ought to inform how we should assess those with advanced bilateral glaucoma. 27 …”
Section: The Burden Of Glaucomamentioning
confidence: 99%